2012
DOI: 10.1177/193229681200600109
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Study of Severe Hypoglycemia Requiring Emergency Medical Service Assistance Reveals Unique Findings

Abstract: Abbreviations: (AI) adrenal insufficiency, (CGM) continuous glucose monitoring, (CI) confidence interval, (CLD) chronic liver disease, (CSII) continuous subcutaneous insulin delivery, (DM) diabetes mellitus, (EMS) emergency medical services, (ER) emergency room, (ERT) emergency room transportation, (ESRD) end-stage renal disease, (HR) hazard ratio, (IQR) interquartile range, (MDI) multiple daily insulin injection, (non-DM) with no diabetes mellitus, (OAA) oral antihyperglycemic agents, (SD) standard deviation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
2
14
2
2
Order By: Relevance
“…This study also supplements the finding of significant long-term mortality in patients with diabetes requiring emergency care reported in a similar study from the USA 16 17. The 1-year mortality seen in this study was comparable to that reported 16 17.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study also supplements the finding of significant long-term mortality in patients with diabetes requiring emergency care reported in a similar study from the USA 16 17. The 1-year mortality seen in this study was comparable to that reported 16 17.…”
Section: Discussionsupporting
confidence: 89%
“…The 1-year mortality seen in this study was comparable to that reported 16 17. Additionally in that study, age and comorbidities were predictors of long-term mortality as in this study, but in contrast hospitalisation was not.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The transported patient was more in Un-Saudi, therefore maybe Saudi depend on transportation by they're on cars.However, protocol insists on transporting all the patient.A condition like hypoglycemia, the patient should be transferred to get suitable care, maybe EMS don't know the consequences for not transfer hypoglycemia patient where most of EMS have a diploma.In Germany,The Nontransported patient with type 1 diabetes increased from 8% to 25%. 6,13 In West Hampshire, UK, paramedics were trained to direct the majority of diabetes patients with hypoglycemia to community diabetes services and patients were taken to the ED only when "necessary;" after the introduction of the protocol, 23% of 291 patients experiencing a hypoglycemic episode were referred to the community diabetes specialist team, and non-transport to hospital increased from 12% to 40% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, hypoglycaemia is frequently also observed in patients without diabetes [1]. Hypoglycaemia in patients without diabetes has been supposed to be associated with a high mortality rate [2, 3]. In hospitalized patients without diabetes, the risk of developing hypoglycaemia is associated with malnutrition, malignancy, renal disease, congestive heart failure, and sepsis [4].…”
Section: Introductionmentioning
confidence: 99%